Leber's Hereditary Optic Neuropathy: Novel Views and Persisting Challenges - Jancic, Jasna; Samardzic, Janko; Stojanovic, Stevan; Stojanovic, Amalija; Milanovic, Ana M.; Nikolic, Blazo; Ivancevic, Nikola; Kostic, Vladimir (CNS & Neurological Disorders - Drug Targets, 2017)
Background & Objective: Leber's hereditary optic neuropathy is an inherited form of optic neuropathy, genetically and pathophysiologically based on mitochondrial insufficiency causing bilateral loss of central vision mostly amongst young adults. Despite being one of the most common mitochondrial diseases, the explanation for its pathophysiological background and effective clinical solutions remain elusive. Widening the scope in the search for pathological findings beyond the optic system has yielded several non-ophthalmologic findings, which might imply that Leber's hereditary optic neuropathy is in fact a multi-systemic disease. Conclusion: The aim of this review is to provide an overview of literature regarding the epidemiology, etiology, pathogenesis, clinical features, diagnostics and possible treatment options and drug targets, as well as presenting challenges related to the disease and proposing a diagnostic algorithm based on current clinical experience.
Keywords: etiopathogenesis